Effect of high somatic cell counts on the sensory acceptance and consumption intent of pasteurized milk and coalho cheese - Bezerra, Joadilza Da Silva; Sales, Danielle Cavalcanti [UNESP]; Oliveira, Juliana Paula Felipe De; Silva, Yhêlda Maria De Oliveira; Urbano, Stela Antas; Lima, Dorgival Morais De; Borba, Luís Henrique Fernandes; Macêdo, Cláudia Souza; Anaya, Katya; Rangel, Adriano Henrique Do Nascimento (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2020)
Our aim was to evaluate the sensorial acceptance and consumption intent of pasteurized milks and coalho cheeses produced with milk with low (80,000 cells/mL) and high (480,000 cells/mL) somatic cell count (SCC) level. Low SCC pasteurized milk (LCC) obtained statistically higher scores on the aroma, consistency, flavor and overall liking attributes in comparison with high SCC pasteurized milk. LCC mean scores for all attributes were statistically higher than high SCC Coalho Cheese. High SCC in raw milk has a detrimental effect on the quality of pasteurized milk and coalho cheeses as it presented lower sensory acceptance, failing to meet the consumer’s desired expectations.
Keywords: consumer; dairy product; mastitis; raw milk